Cognitive Ability as a Non-modifiable Risk Factor for Post-prostatectomy Urinary Incontinence: A Double-Blinded, Prospective, Single-Center Trial - Reichert, Mathias; Popeneciu, Ionel Valentin; Uhlig, Annemarie; Trojan, Lutz; Mohr, Mirjam Naomi (Frontiers in Surgery, 2022)
Introduction: Urinary incontinence (UI) is a wide-spread and feared side-effect of conventional or even robot-assisted radical prostatectomy (RALP) due to its high impact on patients´ quality of life (QoL). Non-modifiable risk factors for UI have already been identified – on surgical and patient side. Yet, to our knowledge, focus thus far has not been placed on functional aspects regarding general cognitive ability. Material & Methods: This is an observational single-center, prospective, double-blinded evaluation of 109 RALPs performed between 07/2020 and 03/2021. All patients underwent a Mini Mental State Examination (MMSE) prior to surgery to evaluate their cognitive ability. Early post-prostatectomy incontinence (PPI) was evaluated using a standardized 1 h pad test performed 24 h after removal of the urinary catheter. The association between MMSE results and PPI were evaluated using univariate and multivariate logistic regression models. Results: Multivariate logistic regression analyses identified MMSE results and nerve sparing (NS) as independent predictors for PPI in patients with an intermediate MMSE result (25-27 points) having a 3.17 times higher risk of PPI when compared to patients with a good MMSE result (≥28) (95% Confidence Interval (CI): 1.22-9.06, p=0.023), while patients without NS had a 3.53 times higher risk of PPI when compared to patients with NS (95% CI: 1.54-11.09, p=0.006). Conclusion: A lower cognitive ability should be treated as a non-modifiable risk-factor for early PPI. In the future it could find its place as a clinical screening tool to identify patients who require more attention especially in the pre-, but also in the postoperative phase.